Design of xanthone propionate photolabile protecting group releasing acyclovir for the treatment of ocular herpes simplex virus - Blake, Jessie A. (2012)
We have attached the antiviral drug acyclovir (ACV) to a xanthone photolabile protecting group (or photocage) through the O6 position of acyclovir, a procedure designed for the treatment of ocular herpes simplex virus infections. Acyclovir is photoreleased from the photocage, under physiological conditions, with a quantum yield (ΦACV release) of 0.1-0.3 and an uncaging cross section (Φ·ε) of 450?1350 M cm−1. We demonstrate that this photorelease method outcompetes alternative reaction pathways, such as protonation. Furthermore, complete release of the drug is theoretically possible given a sufficient dose of light . Surprisingly the acyclovir photocage, also showed some antiviral activity towards HSV-1.